The First World Congress on Tourette Syndrome and Tic Disorders: Controversies and Hot Topics in Etiology and Treatment - Mathews, Carol A.; Stern, Jeremy S. (Frontiers in Neuroscience, 2016)
The first World Congress on Tourette Syndrome and Tic Disorders was held in London, June 2016 by the Tourette Association of America, Tourettes Action (UK) and the European Society for the Study of Tourette Syndrome. Presentations arising from large-scale collaborative projects were an important component of the scientific programme. This article focuses on areas raised in the hot topics session and two moderated debates, which covered emerging research in etiology and treatment. The hot topics ranged across genetics, arguably including the first confirmed Tourette Syndrome (TS) susceptibility gene NRXN1, neurocognition and neurophysiology, including the possibility of a neurocognitive endophenotype for TS and the use of depth and cortical surface electrodes to investigate the neurophysiology of tics on the background of the evolving field of deep brain stimulation, to novel treatment approaches such as dental orthotics and an online behavioural intervention. The debates aired controversies in treatment; pharmacotherapy versus behavioural treatment and the place of medical cannabinoids. These sessions demonstrate the vibrancy of a field that has considerably expanded in the last decade, the significant progress that has been made and the direction that some of the most fruitful next phases of research will take.